Preliminary Analysis Report: Characterization of Aquaculture in Kenya - Juma, Fredrick; Brako Dompreh, Eric; Manyise, Timothy; Munguti, Jonathan; Adhiambo, Rael; Iteba, Jacob; Muthoka, Mavindu; Mungai, Daniel (WorldFish, 2024)
The aquaculture sector in Kenya is recognized as a critical pillar for advancing food security, economic growth, and poverty alleviation, particularly in rural communities. With its rapid expansion globally as the fastest-growing food production sector, aquaculture offers a sustainable alternative to traditional fisheries, which face significant challenges due to overfishing and environmental degradation. In this context, WorldFish, in collaboration with Hydro Victoria, initiated characterization of aquaculture study that aimed at providing an indepth understanding of the sector’s dynamics across Kenya's three main aquaculture regions: the Lake Region, Central Region, and Coastal Region. Conducted from 19th August, 2024, to 30th August, 2024, 5,258 fish farming households were reached out during the survey, making it one of the most extensive studies of its kind in Kenya. The study covered a diverse range of counties, including Kisumu, Busia, Siaya, Homabay, and Kakamega in the Lake Region; Nyeri, Kirinyaga, Meru, Tharaka-Nithi, and Embu in the Central Region; and Kilifi, Taita Taveta, Kwale, and Mombasa in the Coastal Region. These regions were selected for their varying levels of aquaculture production potential and unique environmental conditions, offering a comprehensive view of the sector across different geographical contexts.